EFFECTIVENESS OF THE REFLECTION-BASED RECIPROCAL TEACHING APPROACH FOR READING COMPREHENSION ACHIEVEMENT IN UPPER SECONDARY SCHOOL IN MYANMAR (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2024)
This study investigates the effectiveness of the reflection-based reciprocal teaching approach in enhancing reading comprehension achievement among upper secondary school students in Myanmar. The reflection-based reciprocal teaching approach is a pedagogical strategy that promotes active engagement, collaborative learning, and metacognitive awareness among students.The research employs a quasi-experimental design, involving a treatment group that receives instruction using the reflection-based reciprocal teaching approach and a control group that receives traditional instruction. The study examines the impact of the intervention on students' reading comprehension skills, as measured by pre- and post-tests, and explores students' perceptions and experiences with the intervention through qualitative methods.Preliminary findings suggest that the reflection-based reciprocal teaching approach significantly improves students' reading comprehension achievement compared to traditional instruction methods. Moreover, qualitative data reveal positive perceptions among students regarding the approach, highlighting its efficacy in enhancing comprehension strategies, fostering critical thinking, and promoting collaborative learning.This research contributes to the growing body of literature on innovative teaching methods for improving reading comprehension outcomes in diverse educational settings. The findings have implications for curriculum development and instructional practices aimed at enhancing students' reading proficiency and overall academic success in Myanmar's upper secondary schools.